THE EFFECT OF DL-METHIONINE SUPPLEMENTATION ON BODY WEIGHT GAIN, FEED CONSUMPTION AND FEED EFFICIENCY OF BROILERS - Deddyano Kandido Son; Charles Venirius Lisnahan; Oktovianus Rafael Nahak (Journal of Tropical Animal Science and Technology, 2020)
The purpose of this experiment was to know the effect of dl-methionine supplementation in feed on the body weight gain, feed consumption, and feed efficiency of broilers. The experiment was conducted at the Laboratory of Animal Husbandry Study Program, Agricultural Faculty, University of Timor, Kefamenanu from December 2019 to January 2020. The experiment used 80 fourteen-day broilers. The method used in this research was an experimental method with a completely randomized design (CRD) consisting of 4 treatments and 4 replications. The treatments given were: T0 (control feed), T1 (T0 + 0.30% dl-methionine), T2 (T0 + 0.50% dl-methionine), and T3 (T0 + 0.70% dl-methionine). The variables observed were body weight gain, feed consumption, and feed efficiency. The results of the experiment showed that the treatment significantly affected the body weight gain, feed consumption, and feed efficiency of broilers (P<0.05). It was concluded that commercial feed supplemented with dl-methionine by 0.70% increased the growth performance of broilers.